15.6k views
0 votes
Solve:
-(x -8) =2
X=

User Gomisha
by
5.2k points

2 Answers

3 votes

Answer:

x = 6

Explanation:

-(x - 8) = 2

multiply the negative

-x + 8 = 2

subtract 8 from both sides

-x = -6

x = 6

User Slorello
by
4.9k points
5 votes

Answer:

x = 6

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define Equation

-(x - 8) = 2

Step 2: Solve for x

  1. Divide both sides by -1: x - 8 = -2
  2. Add 8 on both sides: x = 6

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: -(6 - 8) = 2
  2. Subtract: -(-2) = 2
  3. Multiply: 2 = 2

Here we see that 2 does indeed equal 2.

∴ x = 6 is the solution to the equation.

User Prototypical
by
5.0k points